An Evaluation of the Effectiveness of the Office of the Auditor General in Promoting Sound Public Sector Auditing in Zimbabwe - Ndlovu, Khotso M. (Midlands State University, 2017)
Auditor General’s offices are known as Supreme Audit Institutions whose main mandate is to act as watchdogs of the national purse and as such play a pivotal role in ensuring efficient, economic and effective use of public resources and moneys. The main thrust of the study is to proffer a critical evaluation of the office of the Auditor General in promoting sound public sector management in Zimbabwe. The key argument of the study is that the legislative framework has a vital bearing not only in promoting sound and up to date public sector auditing but also in ensuring that values of accountability and transparency are upheld in the public sector domain. To this end the study intends to meet these objectives: to examine the performance of the Auditor General in Zimbabwe, to critically analyse various factors that are militating against the operations of the Auditor General, to analyse the relevant legislative framework and its bearing on the performance of the Auditor General’s office and most importantly to examine the independence of the office of the Auditor General in discharging her duties as well as to proffer recommendations aimed at improving the performance of the Auditor General’s office in Zimbabwe. The study acknowledges that the Audit Office Act chapter 22:18 passed in 2010 and Public Finance Management Act chapter 22:19 in addition to the constitution are a milestone achievement to revamp public expenditure management system in Zimbabwe. These are however not sufficient particularly in safeguarding the independence of the Auditor General as the legal framework still contains some counter provisions. The study noted that lack of sanctioning and prosecutorial powers, tedious public sector operating procedures, unattractive remuneration and lack of cooperation on the part of the treasury; accounting officers and government ministers to a greater extent negatively affect the Audit General’s ability to discharge her duties in an effective, objective and efficient manner. In an attempt to promote sound public sector auditing the study suggested various initiations that include revision of the regulatory framework, simplification of public sector standard operating procedures and improving remuneration.